In-situ temperature-dependent characterization of copper through glass via (TGV). (February 2022) - Pan, Ke; Xu, Jiefeng; Lai, Yangyang; Park, Seungbae; Okoro, Chukwudi; Joshi, Dhananjay; Pollard, Scott
Abstract: Glass has been proposed as a promising material for interposer because of its outstanding material properties. The development of through-glass via (TGV) technology is the most challenging process in the fabrication of glass interposers. This study investigates thermomechanical responses of TGVs induced by thermal loading. Optical profilometry was used to measure the protrusion of copper vias during thermal cycling. The TGV was heated from room temperature (RT) 23 °C to 400 °C and then cooled to RT. The height of an irreversible copper protrusion was recorded at different temperatures. In-plane deformation of the glass caused by thermal mismatch is investigated. Two-dimensional digital image correlation (2D DIC) was applied to measure the in-plane deformation of the glass near the copper via during thermal cycling. The in-plane displacement of the glass near copper vias reached its maximum around 250 °C, then started decreasing because of the copper protrusion and the significant creep of copper material at elevated temperatures. The effect of temperature ramp rate (4 °C/min, 15 °C/min, 30 °C/min, 50 °C/min) on the in-plane deformation of the glass was studied. The in-plane deformation of the glass can be reduced be applying slower ramp rate, because more significant creep occurs in the copper with slower ramp rate which alleviates the CTE mismatch-induced thermal stress at the copper-glass interface. Measurements were conducted to study the creep behavior of the copper via at different temperatures with one hour duration. Each of four TGV samples was heated to a peak temperature, 100 °C, 200 °C, 300 °C, and 400 °C, respectively, and the temperatures were held for 1 h. The glass in-plane displacements were measured by a 2D DIC. Numerical simulations were performed to provide an insight into the thermomechanical behavior of the copper vias and the glass during thermal cycling. The equivalent creep strain of the copper and the maximum principal stress of the glass are presented based on the simulation results. Highlights: In-situ deformation/strain/stress results of TGV samples during thermal cycling Microscale field of view with high temperature deformation measurement In-situ copper protrusion measurement at high and low temperatures